Nb/Au/NbSe2 hybrid Josephson junctions. (7th October 2021) - Tian, Wanghao; Chen, Shixian; Xu, Zuyu; Li, Dingding; Du, Hongmei; Wei, Zihan; Wu, Kaixuan; Sun, Hancong; Dong, Sining; Lv, Yangyang; Wang, Yong-Lei; Koelle, Dieter; et al.
Abstract: We fabricated thin film Nb/Au/NbSe2 hybrid Josephson junctions by a dry transfer technique with only a single lithography step in the process. A thin Au layer is deposited on Nb to prevent oxidation during the fabrication process. The superconducting van der Waals (vdW) material NbSe2 is placed on top of the Nb/Au layer. Electrical transport properties are studied in detail and are compared to numerical simulations. The current–voltage characteristics we observe are typical for superconductor-normal metal-superconductor junctions and we do not observe an effect of a potential insulating barrier between NbSe2 and Au. The modulation of the critical current in magnetic fields indicates an inhomogeneous distribution of supercurrent density, presumably caused by the roughness of the Nb/Au interface to NbSe2 . Nevertheless, we observe clear integer Shapiro steps, indicating a sinusoidal current phase relation of junctions. We do not see an impact of the anisotropic s -wave and the charge density wave in NbSe2 on the Josephson effects. Our method presents a viable and simple way to fabricate hybrid Josephson junctions between superconducting films and two-dimensional (2D) vdW superconducting materials, which might offer a chance for widespread applications.